Revised Charter of the City of Elmira 17, 20-22 (1898) - (:unkn) unknown (My University, 1898)
Elmira City Charter, Title 3-Powers and Duties of the Common Council, § 26, pts. d, e, & k: Granted the Common Council the power to regulate firearm discharge and gun powder storage
Keywords: DISCHARGE; GUNPOWDER - STORAGE